Pendugaan Viabilitas benih padi (Oryza sativa L.) dengan Uji Tetrazolium: Viability of Rice Seeds (Oryza sativa L.) Via The Tetrazolium Test - Wati Tri Utami; Asih Farmia; Suharno Suharno (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2024)
Supporting factors for the success of rice planting include seed availability in sufficient quantities, high quality, and availability when needed. Conventional rice seed viability testing generally takes quite a long time, around 14 days. Therefore, it is necessary to develop several methods for quickly testing seed viability. This research aims to determine the coloring pattern of rice seeds, differences in viability tested with 0.25% tetrazolium concentration, and the relationship between the viability values of seeds tested for sprouting and those tested with 0.25% tetrazolium. This research was carried out from March to May 2023 at the Laboratory of the Central Java Seed Supervision and Certification Center. The treatments used were tests using the direct sprout test (rolled paper in plastic test) and the 0.25% concentration tetrazolium test method. The seeds used were seeds with different storage times (0, 1, 2, and 3 months) to obtain variations in seed vigor. The data obtained were analyzed using visual and descriptive analysis, t-test, and correlation analysis. The results showed that the tetrazolium test with a concentration of 0.25% on Inpari 42 rice seeds produced seven coloring patterns grouped into four viable seed and three non-viable seed coloring patterns. The 0.25% concentration tetrazolium test showed that the results had no significant effect and were closely related the results of the direct germination test so the rapid test could be used as a substitute for the (conventional) germination test on a wide scale.